Preoperative Opioid Utilization Patterns and Postoperative Opioid Utilization: A Retrospective Cohort Study. (December 2021) - Rishel, Chris A.; Angst, Martin S.; Sun, Eric C.
Abstract : Background: Among chronic opioid users, the association between decreasing or increasing preoperative opioid utilization and postoperative outcomes is unknown. The authors hypothesized that decreasing utilization would be associated with improved outcomes and increasing utilization with worsened outcomes. Methods: Using commercial insurance claims, the authors identified 57, 019 chronic opioid users (10 or more prescriptions or 120 or more days supplied during the preoperative year), age 18 to 89 yr, undergoing one of 10 surgeries between 2004 and 2018. Patients with a 20% or greater decrease or increase in opioid utilization between preoperative days 7 to 90 and 91 to 365 were compared to patients with less than 20% change (stable utilization). The primary outcome was opioid utilization during postoperative days 91 to 365. Secondary outcomes included alternative measures of postoperative opioid utilization (filling a minimum number of prescriptions during this period), postoperative adverse events, and healthcare utilization. Results: The average age was 63 ± 13 yr, with 38, 045 (66.7%) female patients. Preoperative opioid utilization was decreasing for 12, 347 (21.7%) patients, increasing for 21, 330 (37.4%) patients, and stable for 23, 342 (40.9%) patients. Patients with decreasing utilization were slightly less likely to fill an opioid prescription during postoperative days 91 to 365 compared to stable patients (89.2% vs . 96.4%; odds ratio, 0.323; 95% CI, 0.296 to 0.352; P < 0.001), though the average daily doses were similar among patients who continued to utilize opioids during this timeframe (46.7 vs . 46.5 morphine milligram equivalents; difference, 0.2; 95% CI, –0.8 to 1.2; P = 0.684). Of patients with increasing utilization, 93.6% filled opioid prescriptions during this period (odds ratio, 0.57; 95% CI, 0.52 to 0.62; P < 0.001), with slightly lower average daily doses (44.3 morphine milligram equivalents; difference, –2.2; 95% CI, –3.1 to –1.3; P < 0.001). Except for alternative measures of persistent postoperative opioid utilization, there were no clinically significant differences for the secondary outcomes. Conclusions: Changes in preoperative opioid utilization were not associated with clinically significant differences for several postoperative outcomes including postoperative opioid utilization. Abstract : In a national claims database of 57, 000 chronic opioid users undergoing common surgical procedures, 41, 22, and 37%, respectively, had stable, decreasing, or increasing preoperative opioid utilization (more than 20% change). After adjustment for potential confounders, 96, 89, and 94% of patients with stable, decreasing, or increasing preoperative opioid use utilized opioids (prescriptions filled) between postoperative days 91 and 365. All three groups had similar average daily oral morphine milligram equivalent utilization. Changes in preoperative opioid utilization were not associated with clinically significant differences in postoperative opioid utilization.Supplemental Digital Content is available in the text.